IMPROVING STUDENTS SPEAKING SKILLS: IMPROVING STUDENTS SPEAKING SKILLS - Mukarova, Dilfuza (Журнал иностранных языков и лингвистики, 2022)
We know that speaking skills is one of the most important aspects of learning a foreign language. This article discusses the problems students face in speaking skills in the process of learning English and how to solve them, as well as how they can develop their speaking skills.